Avaliação de parâmetros de memória em modelo animal de obesidade induzido por dieta hiperlipídica - Francisco, Gabriela Guzatti (2016)
Introduction: The obesity rates have reached alarming proportions in the world. In addition to the effects in peripheral tissues, obesity may also affect brain structures leading to cognitive deficits especially related to memory. Objective: Evaluate memory parameters in a model animal of obesity induced by high fat diet. Methods: 40-day-old Swiss mice were randomized into two groups. The control group received control diet and the obese group received high fat diet for 10 weeks. The confirmation of obesity in animals was defined by body weight and visceral fat weight. All animals were submitted to object recognition test and inhibitory avoidance, weighed and then killed through fast decapitation. The abdominal cavity was incised, and the visceral fat was removed. After the brain removal, the hippocampus and prefrontal cortex were separated by dissection for biochemical analysis of acetylcholinesterase activity and mitochondrial respiratory chain. Results: Body weight and mesenteric fat of the animal obese group was higher if compared with controls. The obese animals had no loss in object recognition and aversive memory when compared with controls. Acetylcholinesterase activity presented no difference between the control group and obese in the hippocampus and prefrontal cortex. The activity of complex I, II and IV of the mitochondrial respiratory chain, and creatine kinase of the obese group was inhibited in the prefrontal cortex and hippocampus when compared to the control group. Conclusion: Obesity was able to inhibit the activity of mitochondrial respiratory chain complex and creatine kinase in the prefrontal cortex and hippocampus of obese mice, implying that neuronal energy production may be affected in these animals. However, this inhibition was not enough to affect neither the activity of acetylcholinesterase in these structures nor the recognition memory objects and aversive in this animal model.